Detecting early gastric cancer: Comparison between the diagnostic ability of convolutional neural networks and endoscopists. Issue 1 (2nd June 2020) - Ikenoyama, Yohei; Hirasawa, Toshiaki; Ishioka, Mitsuaki; Namikawa, Ken; Yoshimizu, Shoichi; Horiuchi, Yusuke; Ishiyama, Akiyoshi; Yoshio, Toshiyuki; Tsuchida, Tomohiro; Takeuchi, Yoshinori; Shichijo, Satoki; Katayama, Naoyuki; et al.
Abstract : Objectives: Detecting early gastric cancer is difficult, and it may even be overlooked by experienced endoscopists. Recently, artificial intelligence based on deep learning through convolutional neural networks (CNNs) has enabled significant advancements in the field of gastroenterology. However, it remains unclear whether a CNN can outperform endoscopists. In this study, we evaluated whether the performance of a CNN in detecting early gastric cancer is better than that of endoscopists. Methods: The CNN was constructed using 13, 584 endoscopic images from 2639 lesions of gastric cancer. Subsequently, its diagnostic ability was compared to that of 67 endoscopists using an independent test dataset (2940 images from 140 cases). Results: The average diagnostic time for analyzing 2940 test endoscopic images by the CNN and endoscopists were 45.5 ± 1.8 s and 173.0 ± 66.0 min, respectively. The sensitivity, specificity, and positive and negative predictive values for the CNN were 58.4%, 87.3%, 26.0%, and 96.5%, respectively. These values for the 67 endoscopists were 31.9%, 97.2%, 46.2%, and 94.9%, respectively. The CNN had a significantly higher sensitivity than the endoscopists (by 26.5%; 95% confidence interval, 14.9–32.5%). Conclusion: The CNN detected more early gastric cancer cases in a shorter time than the endoscopists. The CNN needs further training to achieve higher diagnostic accuracy. However, a diagnostic support tool for gastric cancer using a CNN will be realized in the near future.